Less is More in Antidepressant Clinical Trials: A Meta-Analysis of the Effect of Visit Frequency on Treatment Response and Drop-out - Rutherford, Bret R (2013)
OBJECTIVE: We investigated how the number of follow-up visits affects response rates and drop-out among patients in antidepressant trials for Major Depressive Disorder (MDD). DATA SOURCES: Medline, PsycINFO, and PubMed were searched to identify trials contrasting antidepressants to placebo or active comparator in adults with depression. The index terms “depression—drug therapy,” “depressive disorder—drug therapy,” and “antidepressant agents,” in addition to the class and individual generic name of all antidepressants were combined using the ‘or’ operator. Results were limited to 1) English language articles, 2) publication year 1985 or later, 3) age group ≥ 18, and 4) publication types including clinical trials, controlled clinical trials, meta-analysis, multi-center study, randomized controlled trial, or review. STUDY SELECTION: Included articles reported trials of approved antidepressant medications for MDD in outpatients aged 18–65, were 6–12 weeks in duration, and had response rates specified using a standardized measure. Trials were excluded for enrolling inpatients, pregnant women, psychotic subjects, or those with treatment-resistant depression. These criteria allowed 9,189 articles identified in the literature review to be narrowed to 111 reports. DATA EXTRACTION: Demographic characteristics, the number of study visits planned in each treatment cell, duration of active treatment, attrition rates, and response rates to medication and placebo were entered into a database. RESULTS: In a multilevel meta-analysis, active medication vs. placebo (OR 1.96, p < 0.001), active comparator vs. placebo-controlled study design (OR 1.82, p < 0.001), and longer vs. shorter duration (OR 1.87, p < 0.001) were associated with significantly increased odds of treatment response. After controlling for these variables, the number of study visits did not significantly influence response rates (OR 0.97, p = 0.877). The odds of drop-out were significantly decreased for active comparator vs. placebo-controlled trials (OR 0.67, p = 0.002) and longer vs. shorter duration trials (OR 0.54, p = 0.035), while increasing numbers of study visits significantly increased the odds of participant drop-out (OR 2.77, p < 0.001). CONCLUSION: Visit schedules that are much more frequent than are commonly practiced in the community treatment of depression may increase the expense of clinical trials and make them less generalizable to standard clinical treatment.